Synthesis of Benzopyranophenazines via Isocyanide-Based Three-Component Reactions - Ayoob Bazgir; Ali Mohammad Astaraki (E-Journal of Chemistry)
Benzo[a]pyrano[2,3-c]phenazines were synthesized in good yields by a three-component reaction of benzo[a]phenazin-5-oles, isocyanides and dialkyl acetylendicarboxylates In refluxing ethanol.